Drivers of global variation in land ownership. Issue 1 (15th September 2020) - Kavanagh, Patrick H.; Haynie, Hannah J.; Kushnick, Geoff; Vilela, Bruno; Tuff, Ty; Bowern, Claire; Low, Bobbi S.; Ember, Carol R.; Kirby, Kathryn R.; Botero, Carlos A.; Gavin, Michael C.
Abstract : Land ownership shapes natural resource management and social–ecological resilience, but the factors determining ownership norms in human societies remain unclear. Here we conduct a global empirical test of long‐standing theories from ecology, economics and anthropology regarding potential drivers of land ownership and territoriality. Prior theory suggests that resource defensibility, subsistence strategies, population pressure, political complexity and cultural transmission mechanisms may all influence land ownership. We applied multi‐model inference procedures based on logistic regression to cultural and environmental data from 102 societies, 71 with some form of land ownership and 31 with no land ownership. We found an increased probability of land ownership in mountainous environments, where patchy resources may be more cost effective to defend via ownership. We also uncovered support for the role of population pressure, with a greater probability of land ownership in societies living at higher population densities. Our results also show more land ownership when neighboring societies also practiced ownership. We found less support for variables associated with subsistence strategies and political complexity.